Witchcraze : a new history of the European witch hunts - Barstow, Anne Llewellyn (San Francisco, CA : Pandora, a division of HarperCollins, 1994)
A brilliant, authoritative feminist history that examines the unrecognized holocaust--an "ethnic cleansing" of independent women in Reformation Europe--and the residual attitudes that continue to influence our culture. Examines the annihilation of women, under the guise of "witch hunts" in Reformation Europe and the residual attitudes that continue to influence our culture.
Bibliography: p. 227-243.
Keywords: Witchcraft -- Europe -- History